2015
DOI: 10.1098/rsif.2015.0479
|View full text |Cite
|
Sign up to set email alerts
|

How body torque and Strouhal number change with swimming speed and developmental stage in larval zebrafish

Abstract: Small undulatory swimmers such as larval zebrafish experience both inertial and viscous forces, the relative importance of which is indicated by the Reynolds number (Re). Re is proportional to swimming speed (v swim ) and body length; faster swimming reduces the relative effect of viscous forces. Compared with adults, larval fish experience relatively high (mainly viscous) drag during cyclic swimming. To enhance thrust to an equally high level, they must employ a high product of tail-beat frequency and ( peakt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 45 publications
4
79
0
Order By: Relevance
“…A surprising finding was that pressure and net thrust distribution have a dip around 0.7 L. Posterior to the CoM, net thrust is generated along 0.35 -0.6 L and at the tail (0.8 -0.95 L); between these two net thrust zones, low net thrust or even net drag occurs between 0.6 and 0.8 L (figure 6c). This dip is most likely due to recoil caused by fluctuating torques on the body [13]: although the body wave amplitude envelope increases at a steady rate in the fish frame of reference (figure 1b), in the earth frame of reference recoil causes the rate at which the envelope widens to be much lower around 0.6-0.8 L [12], reducing local body speed, peak instantaneous thrust and hence cycle-average thrust between 0.6 and 0.8 L.…”
Section: Flow Regime Affects Thrust Contribution By Edge Vorticesmentioning
confidence: 99%
See 1 more Smart Citation
“…A surprising finding was that pressure and net thrust distribution have a dip around 0.7 L. Posterior to the CoM, net thrust is generated along 0.35 -0.6 L and at the tail (0.8 -0.95 L); between these two net thrust zones, low net thrust or even net drag occurs between 0.6 and 0.8 L (figure 6c). This dip is most likely due to recoil caused by fluctuating torques on the body [13]: although the body wave amplitude envelope increases at a steady rate in the fish frame of reference (figure 1b), in the earth frame of reference recoil causes the rate at which the envelope widens to be much lower around 0.6-0.8 L [12], reducing local body speed, peak instantaneous thrust and hence cycle-average thrust between 0.6 and 0.8 L.…”
Section: Flow Regime Affects Thrust Contribution By Edge Vorticesmentioning
confidence: 99%
“…Larvae from oviparous bony fish swim in the intermediate flow regime, where both inertial and viscous forces are important [7,12,13]. Larvae of virtually all bony-fish species possess a median fin fold that extends along the dorsal, caudal and ventral sides of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The gain of this correction should therefore correlate with propulsive efficacy, both of which increase with age. [20; 21; 22]. Further, the asymmetry of angular velocity correction is consistent with morphological changes, as the ease of nose-up rotation correlates with the convexity of the ventrum [2]; decreasing convexity with the loss of yolk sac from 4 to 7 dpf may underlie the concomitant worsening of nose-down angular velocity cancellation, while the late improvement may arise from increasing ventral convexity by 21 dpf [18].…”
Section: Discussionmentioning
confidence: 89%
“…They 367 also found that a higher curvature could result in a higher escape distance, given a start 368 duration; this corresponds to the weak correlation that we find for speed with head-to-tail 369 angle. For (near-)cyclic swimming of larval fish, the swimming speed was found to increase 370 with increasing tail-beat frequency and to a lesser extent amplitude (Van Leeuwen et al, 2015). 371…”
Section: Producing Acceleration 347mentioning
confidence: 97%